Penuangan Isu Bipolar Disorder dalam Karya Tari In Between - Annisa Shafa Dhiyaliza; Ni Nyoman Kasih; Anak Agung Ketut Oka Adnyana (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
This written work discusses the creation of a choreography titled